Inequality trends in the context of changes in labor market outcomes, composition and redistribution in Germany - Maximilian Blömer; Elena Herold; Max Lay; Andreas Peichl; Ann-Christin Rathje; Paul Schüle; Anne Steuernagel (EconPol Forum, 2024)
We examine how inequality evolved in Germany during the 1983-2020 period. Labor market participation of women increased significantly, while average weekly working hours of women changed little. Gender differences in earnings are still pervasive and more pronounced for individuals with children. Inequality in earnings and disposable household income increased from the 1990s until 2005. Since then, inequality in earnings has decreased, despite labor force compositional changes, such as high rates of net migration, that tend to push up inequality
Keywords: 330